El sistema cardiovascular y la exposición a gran altitud: desde la adaptación a la enfermedad. Parte I - Chacón-Díaz, Manuel (2026)
Exposure to high altitude constitutes a complex physiological challenge, driven primarily by hypobaric hypoxia and, in some settings, by extreme environmental conditions such as severe cold and increased ultraviolet radiation. At the cardiovascular level, this exposure elicits a range of acute and chronic adaptations, including activation of the sympathetic nervous system, pulmonary vasoconstriction, and vascular and ventricular remodelling. In the Andean region, millions of people live at elevations above 2,500 metres above sea level, rendering them particularly susceptible to these physiological adaptations and the associated cardiovascular alterations. This manuscript represents the first part of a narrative review and aims to synthesise the available scientific evidence on mechanisms of adaptation to high altitude, as well as the characteristics of pulmonary hypertension, heart failure, and congenital heart disease observed in both native high-altitude populations and individuals originating from low-altitude areas. In addition, it seeks to identify existing gaps in current knowledge of these conditions in order to promote the development of specific diagnostic, preventive, and therapeutic strategies aimed at improving cardiovascular health among populations residing at or temporarily exposed to high altitude.